Kritik Teologis Al-Ghazali Terhadap Metafisika Filsuf Muslim: Analisis Atas Tiga Pokok Pemikiran Dalam Tahāfut Al-Falāsifah - Ummah, Afdalul; Iqbal, Imam; Irfani, Muhammad Aska (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2025)
The reception of Greek philosophy in the Islamic world through the translation of classical texts sparked debates between rationality and revelation in Islamic intellectual tradition. This study aims to analyze Al-Ghazali’s critique of three main points in the thought of classical Muslim philosophers as outlined in Tahāfut al-Falāsifah: the eternity of the world, the limitation of God's knowledge to universals, and the notion of resurrection involving only the soul. This research employs a qualitative method with a library research approach and content analysis of primary texts and relevant secondary literature. The findings reveal that Al-Ghazali’s critique represents a synthesis between Ash’arite theology and philosophical rationalism, firmly rejecting metaphysical concepts that he deemed incompatible with Islamic faith principles. The study concludes that Al-Ghazali’s critique should not be viewed as a rejection of philosophy per se, but rather as an effort to safeguard the integrity of Islamic doctrine through a systematic theological-philosophical approach. His critique significantly contributes to Islamic philosophical discourse and fosters an epistemological dialogue between reason and revelation.